Reconsidering stress and smoking: a qualitative study among college students. Issue 3 (12th June 2007) - Nichter, Mark; Nichter, Mimi; Carkoglu, Asli; ,
Abstract : Background: Although it is widely acknowledged among adult smokers that increases in smoking are often precipitated by stressful events, far less attention has been given to smoking during times of stress among youth. Aims: To address this gap by drawing attention to the social utility of smoking in contexts associated with stress among college students. Design: Face-to-face semistructured interviews with college freshmen at a large midwestern university in the US. Participants: Male and female low-level smokers (n = 24), defined as those who reported regular weekday smoking (typically 3–4 cigarettes a day) and smoking at parties on weekends, were interviewed once in person. In addition, 40 brief interviews with smokers were conducted during final examination. Measurements: Interviews focused on a range of issues including current smoking behaviour and reasons for smoking. As part of the interview, students were given a deck of cards that listed a range of reasons for smoking. Participants were asked to select cards that described their smoking experience in the past 2 weeks. Those who selected cards that indicated smoking when stressed were asked to explain the reasons why they did so. Results: A review of qualitative responses reveals that smoking served multiple functions during times of stress for college students. Cigarettes are a consumption event that facilitates a brief social interaction during study times when students feel isolated from their friends. Cigarettes also serve as an idiom of distress, signalling non-verbally to others that they were stressed. Students described smoking to manage their own stress and also to help manage "second-hand stress" from their friends and classmates. Conclusions: Moving away from an individual-focused analysis of stress to a broader assessment of the social contexts of smoking provides a more nuanced account of the multifunctionalilty of cigarettes in students' lives. Qualitative research draws attention to issues including the need for smoking and socialising during examination time, smoking as a way to take a break and refocus, notions of second-hand stress and smoking to manage social relationships.